Dilema Etika Guru dalam Menjaga Integritas Penilaian: Studi Fenomenologis: Teachers' Ethical Dilemmas in Maintaining Assessment Integrity: A Phenomenological Study - Fahmi Alizar Nur Fachrudin; Aim AbdulKarim; Rika Sartika (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Assessment integrity is a fundamental principle in education, ensuring the objectivity, fairness, and credibility of learning outcomes. However, teachers often face ethical dilemmas when their professional moral commitments clash with institutional demands, school policies, and parental expectations. This study aims to explore the lived experiences of Pancasila Education teachers as they navigate ethical dilemmas, interpret value conflicts, and make decisions to uphold assessment integrity. The study employs Max van Manen's hermeneutic phenomenological approach. Data were gathered through in-depth interviews with Pancasila Education teachers and school supervisors, then analyzed using Van Manen's stages of thematic reflection. The study reveals that assessment integrity is a dynamic moral decision-making process involving the negotiation of professionalism, institutional policies, and students' interests. Teachers engage in various forms of ethical deliberation through reflection, the use of assessment evidence, dialogue with stakeholders, and the interpretation of spirituality as a source of moral legitimacy when facing dilemmas. These findings expand the moral decision-making model by demonstrating that the moral process is cyclical and influenced by social context, school culture, and professional experience. Assessment integrity is understood not merely as procedural compliance, but as a reflective practice continuously negotiated within the teacher's professional experience. The study contributes theoretically to the fields of phenomenology, moral decision-making, and teacher professional ethics, while underscoring the importance of strengthening ethical literacy in education policy and teacher professional development.